Jaminan Kesehatan Nasional pada Ibu Bersalin: Sebuah Studi Cross Sectional di Nusa Tenggara Timur, Indonesia - Bahaji, Amanda Firdausya; Muhammad, Faris; Ayu, Putri; Davina, Rizani Alia; Yulianty, Vetty (Jurnal Ekonomi Kesehatan Indonesia, 2025)
Maternal Mortality Rate (MMR) in Indonesia remains high, particularly in East Nusa Tenggara (NTT). This study analyzes the relationship between National Health Insurance (JKN) ownership and mothers choosing childbirth facilities in NTT. This study employs a cross-sectional design with a quantitative approach, utilizing secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS), which was conducted from October to November 2024. The study population includes mothers who gave birth in NTT during the 2017 IDHS period, with a sample of 1,236 respondents selected using a stratified two-stage cluster sampling technique. Data analysis was performed using the chi-square test to assess the relationship between JKN ownership as the independent variable and the choice of childbirth facility as the dependent variable. Additionally, covariate variables such as maternal education level, economic status, maternal age, and residential location were analyzed. The results indicate that maternal education level has a significant relationship with the selection of healthcare facilities (p-value < 0.001). However, maternal age (p-value = 0.447), economic status (p-value = 0.199), residential location (p-value = 0.069), and JKN ownership (p-value = 0.110) do not show significant relationships. This study concludes that health education for pregnant women and optimizing the JKN program are necessary to enhance the utilization of healthcare facilities for childbirth and improve healthcare access, particularly in regions such as NTT.